The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.jcim.9b00837
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Uncoupled Carbocyclization and Epimerization Catalyzed by Two Non-Heme Iron/α-Ketoglutarate Dependent Enzymes

Abstract: The non-heme iron/α-ketoglutarate dependent enzymes SnoK and SnoN from Streptomyces nogalater are involved in the biosynthesis of anthracycline nogalamycin. Although they have similar active sites, SnoK is responsible for carbocyclization whereas SnoN solely catalyzes the hydroxyl epimerization. Herein, we performed docking, molecular simulations, and a series of combined quantum mechanics and molecular mechanics (QM/MM) calculations to illuminate the mechanisms of two enzymes. The catalytic reactions of two e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 80 publications
3
6
0
Order By: Relevance
“…The Fe­(IV) = O species in the active site of the nonheme 2OG-dependent enzymes can exist either as a trigonal bipyramidal coordinate (5C) , configuration or octahedral-coordinate (6C) configuration. The QM/MM study of AsqJ and EFE showed that 6C Fe­(IV) = O resembles closely to the experimentally trapped Fe­(IV) = O species obtained in prolyl-4-hydroxylase and taurine dioxygenase (TauD) enzymes. , However, it is not known whether the 5C or 6C is the preferred configuration in T6ODM.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The Fe­(IV) = O species in the active site of the nonheme 2OG-dependent enzymes can exist either as a trigonal bipyramidal coordinate (5C) , configuration or octahedral-coordinate (6C) configuration. The QM/MM study of AsqJ and EFE showed that 6C Fe­(IV) = O resembles closely to the experimentally trapped Fe­(IV) = O species obtained in prolyl-4-hydroxylase and taurine dioxygenase (TauD) enzymes. , However, it is not known whether the 5C or 6C is the preferred configuration in T6ODM.…”
Section: Resultssupporting
confidence: 94%
“…To understand the oxygen activation by Fe­(II), QM/MM calculations were performed on S = 0, S = 1, S = 2, and S = 3 spin state surfaces for the three representative structures obtained from the MD simulations of Fe­(III) super-oxo complex. The quintet state was suggested to be most favorable in the context of 2OG-dependent nonheme iron enzymes from previous experimental electron paramagnetic resonance (EPR) Mössbauer spectroscopy studies and the QM/MM studies; ,,, , therefore, it was chosen as the reference to compute the relative energies of other spin states for T6ODM.…”
Section: Resultsmentioning
confidence: 99%
“…Fe IV is coordinated in a distorted octahedral geometry with the succinate bound in a bidentate fashion. Such an arrangement of the active site was proposed in other studies of non‐haem iron dioxygenases, [56–59] however, depending on the surroundings of the active site, Fe IV can also be in a trigonal bipyramidal arrangement [55, 60–62] or a water molecule can bind to Fe IV as an equatorial ligand [63, 64] . As expected for this complex, the electronic configuration of S is π* xy 1 π* xz 1 π* yz 1 σ*x2-y2 1 (the occupied orbitals are shown in Figure S2 in the Supporting Information), the σ*z2 orbital is virtual and oriented along the O−Fe−N(His‐279) axis and thus able to accept an electron from the substrate during the initial HAT.…”
Section: Resultssupporting
confidence: 60%
“…Such an arrangement of the active site was proposed in other studies of non-haem iron dioxygenases, [56][57][58][59] however,d epending on the surroundings of the actives ite, Fe IV can also be in a trigonal bipyramidal arrangement [55,[60][61][62] or aw ater molecule can bind to Fe IV as an equatorial ligand. [63,64] As expected for this complex, the electronic configurationo fS is p* xy…”
Section: Initial Hatf or The Native Substratessupporting
confidence: 74%
“…The QM/MM method has been applied in the studies of mononuclear iron-containing enzymes. In our calculations, the whole system was divided into QM and MM regions. All QM/MM calculations were conducted by employing the ChemShell package, which combines TURBOMOLE and DL_POLY programs for treating the QM and MM regions, respectively.…”
Section: Computational Detailsmentioning
confidence: 99%